Assessing the readiness for the implementation of Generally Recognised Accounting Practice (GRAP) in the Department of Transport and Public Works in the Western Cape - Solomons, Yolanda M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2012.